Depression among Adolescents in Kuching, Malaysia - Ang, Ai Ling (Japan Peadictric Society, 2018)
Background: The trend of adolescent depression is on the rise worldwide. There is limited research on mental health among adolescents, especially on adolescent depression in Malaysia. The study aimed to estimate the prevalence and identify the factors associated with depression among adolescents in Kuching, Malaysia. Methods: A cross-sectional study was conducted on 320 students from urban and rural public secondary schools in Kuching, Malaysia from 1st April 2013 to 31st May 2013. The students randomly selected via multi-stage sampling completed the Malay version of Child Depression Inventory (CDI) and Beck Scale for Suicidal Ideation (BSS). Results: The prevalence of depression in this study is 26.2%. Binary logistic regression analysis showed that variables significantly associated with depression were race (p=0.028), type of class (p<0.001), mother's education level (p=0.036), type of housing (p=0.036), parents' marital status (p=0.012), alcohol intake (p=0.005), stealing (p<0.001) and history of disciplinary record (p=0.005). Variables that remain significant with multivariable logistic regression were type of class (p=0.004), parents' marital status (p=0.017) and stealing (p<0.001). Students from Arts stream (OR=2.430) with parents who had separated, divorced or widowed (OR=3.128) and had history of stealing (OR=3.271) were predicted to be at risk for depression. There is significant correlation between total CDI score and total BSS score (p<0.001). Conclusions: The prevalence of depression among adolescents is high and comparable to several regional and international studies. Depression is significantly correlated with suicidal ideation. There is a need for greater collaboration and efforts among various agencies to enhance mental health promotion among adolescents.